Volume Charge Density in Mixed Number Lorentz Transformation - Bhuiyan, S. A. (Journal of Scientific Research, 2019)
We know charge density is changed when it observes from a moving frame of reference due to the length contraction. In this paper we have studied the volume charge density in special and mixed number Lorentz transformation. We also investigate the changes of the volume charge density of moving system in terms of rest system in mixed number Lorentz Transformations at different angles and velocities.